(untitled) (REMUNOM, 2024)
The rural roads are essential for the flow of agricultural production and the connectivity of rural areas, especially in Brazil. In the municipality of Gurupi, TO, the Avenida Parque and Barroquinha roads play a crucial role in rural logistics and must be constantly assessed to ensure a good level of quality. This study aimed to evaluate the condition of these roads using the ICMNP method (Non-Paved Road Maintenance Condition Index) developed by DNIT. The evaluation was carried out through visual field inspections, conducted at the beginning of the rainy season. Defects such as inadequate cross-sections, poor drainage, corrugations, excess dust, potholes, and wheel ruts were analyzed and classified into high, medium, or low severity levels. The final classification of the roads was obtained by calculating the ICMNP, determining the condition of the roads. The results showed that Barroquinha road was classified as regular, with defects such as corrugations, insufficient drainage, and lateral erosion. Avenida Parque was classified as good, but also showed lack of drainage and signage. Both sections face issues related to inadequate drainage, which affects the durability of the roads. It is concluded that investments in drainage, surfacing, and signage are essential to improve the condition of these roads and, consequently, enhance logistical efficiency and local agricultural economy, promoting the sustainable development of the region.